Sacrifice, scripture, and substitution: readings in ancient Judaism and Christianity : [first delivered as papers in June 2002 at Purdue University in connection with the annual meeting of the Colloquium on Violence and Religion] - Astell, Ann W.; Goodhart, Sandor ca. 20./21. Jh. (Christianity and Judaism in antiquity, 2011)
Substitutive reading : an introduction to Girardian thinking, its reception in biblical studies, and this volume / Sandor Goodhart and Ann W. Astell -- Part I. Sacrifice -- ch. 1. Mimesis, sacrifice, and the Bible : a conversation with Sandor Goodhart / René Girard -- ch. 2. Bloody logic : the biblical economy of sacrificial substitution and some of its eucharistic implications / Thomas Ryba -- ch. 3. Aspects of the transformation of sacrifice in Judaism / Michael Fishbane -- ch. 4. The Eucharist and the mimesis of sacrifice / Bruce Chilton -- ch. 5. Eucharistic origins : from the New Testament to the liturgies of the golden age / Robert Daly -- ch. 6. Life after death : violence, martyrdom, and academic life in Western religions / Alan F. Segal -- ch. 7. Anti-Judaism, Josephus, and the Hellenistic-Roman period / Louis H. Feldman -- ch. 8. Beyond anti-Judaism : Louis Feldman and the 'lachrymose version' of Jewish history / Erich S. Gruen -- ch. 9. Mimesis, scapegoating, and philo-Semitism : reading Feldman and Girard / Stuart D. Robertson -- Part II. Scripture -- Section 1. hebrew scripture : Genesis 22 -- ch. 10. Creation and akedah : blessing and sacrifice in the Hebrew scriptures / Matthew Pattillo -- ch. 11. The unbinding of Isaac / Steven Stern -- ch. 12. Binding and blessing : a response to Pattillo and Stern / Sandor Goodhart -- Section 2. Holy writings : the book of Job -- ch. 13. Mimesis, sacrifice, and the wisdom of Job / Chris Allen Carter -- ch. 14. The expulsion of complaint from early Jewish worship / William Morrow -- ch. 15. The Book of Job and the problem of evil : reading from theodicy to the ethical / Sandor Goodhart -- Section 3. Christian Gospel : Matthew, Luke, and John -- ch. 16. Luke and the opportune time : reading the temptation story as preface to kingdom and prologue to passion / William Martin Aiken -- ch. 17. A gospel that preaches nonviolence and yet provokes violence / Gérard Rossé -- ch. 18. 'Exilic' identities, the Samaritans, and the 'Satan' of John / Ann W. Astell -- Section 4. Christian Epistles : colossians and Hebrews -- ch. 19. Aristotle's 'natural slaves' and Colossae's unnatural 'Scythians' : a generative exegesis of Colossians 3:11 / Christopher S. Morrissey -- ch. 20. Is an anti-sacrificial reading of Hebrews plausible? / Poong-In Lee -- ch. 21. Hermeneutics, exegesis, and René Girard : a response to Christopher Morrissey and Poong-in Lee / Anthony W. Bartlett